1978
DOI: 10.1295/polymj.10.619
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of the Poly(1-olefin)s. Thermal Behavior and Dilute Solution Properties.

Abstract: Poly(l-olefin)s from poly(l-butene) up to poly(1-octadecene) have been characterized. The melting point was measured by Differential Scanning Calorimetry (DSC-1B) and dilatometry, the specific volume and volume expansion coefficient by dilatometry, and the unperturbed chain dimension by intrinsic viscosity at near theta conditions. A trend is confirmed for melting points and revealed for expansion coefficients of first a decrease with increasing side-chain length in the polyolefins, followed by an increase wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The small Δ H f values of poly(1‐hexene) and poly(1‐octene) propose the crystallizing limitation for long lateral POs. This may be one of the reasons why poly(1‐hexene) and poly(1‐octene) were reported mostly without melting point 1…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The small Δ H f values of poly(1‐hexene) and poly(1‐octene) propose the crystallizing limitation for long lateral POs. This may be one of the reasons why poly(1‐hexene) and poly(1‐octene) were reported mostly without melting point 1…”
Section: Resultsmentioning
confidence: 99%
“…In general, all higher α‐olefins can be polymerized by the various classes of Ziegler–Natta catalysts to mainly isotactic polymer 1–4. The polymerization rate decreases with increasing steric requirements, that is, both mere chain length in straight‐chain olefins leads to decrease, as does branching near to the double bond.…”
Section: Introductionmentioning
confidence: 99%
“…2,5,14 X-ray diffraction analysis revealed that side-chain crystallinity predominates with an increasing num- ber of methylene groups for the higher homologues of the poly-␣-olefins. Wang et al 14 showed that side-chain crystallization occurs at least from poly-1-tridecene. In contrast to poly-1-pentene, the first heating cycle did not destroy the crystal structure of the higher poly-␣olefins prepared with 1, and the melting points of poly-1-decene, poly-1-tetradecene, and poly-1-octadecene could still be observed during the second heating cycle.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…It is well known that, various classes of Ziegler-Natta catalysts can polymerize all higher alpha olefins, and mostly isotactic polymers are formed. [3][4][5][6] It is known that the type of prepolymer produced has a strong influence on the growth mechanism of the catalyst particle, but the extremely low-yield prepolymerization of higher alpha olefins and its influence on the final polymer morphology in a second liquid propylene polymerization has never been studied in open literature.…”
Section: Introductionmentioning
confidence: 99%